# Use special products to expand and simplify: 5x^m(x^(m+1) + 3)^2Show solution and explain the answer.

*print*Print*list*Cite

Expert Answers

sciencesolve | Certified Educator

You need to expand binomial `(x^(m+1) + 3)^2` using the formula `(a+b)^2 = a^2 + 2ab + b^2` such that:

`(x^(m+1) + 3)^2 = (x^(m+1))^2 + 2*3*x^(m+1) + 3^2`

`(x^(m+1) + 3)^2 = (x^(2m+2)) + 6x^(m+1) + 9`

You need to multiply the expanded binomial by `5x^m` such that:

`5x^m*(x^(m+1) + 3)^2 = 5(x^m*x^(2m+2)) + 30x^m*x^(m+1) + 45x^m`

`5x^m*(x^(m+1) + 3)^2 = 5(x^(m+2m+2)) + 30x^(m+m+1) + 45x^m`

`5x^m*(x^(m+1) + 3)^2 = 5(x^(3m+2)) + 30x^(2m+1) + 45x^m`

**Hence, simplifying the product yields `5x^m*(x^(m+1) + 3)^2 = 5(x^(3m+2)) + 30x^(2m+1) + 45x^m` .**